2019
DOI: 10.1002/smtd.201900653
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Atom Ru Doping Induced Phase Transition of MoS2 and S Vacancy for Hydrogen Evolution Reaction

Abstract: Using electrochemical water splitting to produce hydrogen is still a grand challenge due to the lack of economical and efficient Pt‐free catalysts. Herein, a single‐atom Ru supported on MoS2 (SA‐Ru‐MoS2) electrocatalyst for the hydrogen evolution reaction (HER) is reported. Results indicate that single‐atom Ru doping induces phase transition of MoS2 and generation of S vacancies, which significantly improve the performance of inert 2D MoS2 for HER. In particular, the SA‐Ru‐MoS2 electrocatalyst exhibits a low o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
205
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(222 citation statements)
references
References 67 publications
4
205
0
Order By: Relevance
“…The HER activity could be improved by designing large numbers of well-defined atomically dispersed active sites hosted over transition metal dichalcogenide materials, such as MoS 2 (111)(112)(113)(114)(115). For instance, carbonized polyacrylonitrile-immobilized single molecular MoS 2 (MoS 2 -cPAN) was demonstrated with much higher turnsover frequency (TOF) to HER than bulk MoS 2 (Fig.…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 99%
“…The HER activity could be improved by designing large numbers of well-defined atomically dispersed active sites hosted over transition metal dichalcogenide materials, such as MoS 2 (111)(112)(113)(114)(115). For instance, carbonized polyacrylonitrile-immobilized single molecular MoS 2 (MoS 2 -cPAN) was demonstrated with much higher turnsover frequency (TOF) to HER than bulk MoS 2 (Fig.…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 99%
“…Here, different synthetic strategies for single metal atom-doped MoS 2 are summarized and discussed ( Fig. 2a-f [36][37][38][39][40][41]).…”
Section: Synthesismentioning
confidence: 99%
“…Recently, this method has been applied in the preparation of several SA-doped MoS 2 catalysts. For example, Zhang et al [36] reported an SA-Ru doped MoS 2 electrocatalyst that was formed using a one-step impregnation method. As shown in Fig.…”
Section: Wet Chemical Impregnationmentioning
confidence: 99%
See 1 more Smart Citation
“…By theoretical calculations, it revealed that the doped Pt atoms can increase the electronic states around the Fermi level, thus tuning the ΔG H* of S atoms neighboring the doped Pt to favor the HER activity. In addition, Zhang et al [23] synthesized singleatom Ru-doped MoS 2 (SA-Ru-MoS 2 ). It induced phase transition from 2H-MoS 2 to 1T-MoS 2 and generated S vacancies, resulting a low η of 76 mV at 10 mA cm À 2 in alkaline media, as shown in Figure 3a and b.…”
Section: Heteroatom Dopingmentioning
confidence: 99%